EVALUATION OF THE USE OF PARTOGRAPH BY MIDWIFE IN DELIVERY MONITORING IN MIDWIVES IN PASAMAN BARAT DISTRICT, 2022 - Timmy Larasati; Sesmi Nanda Oktavia; Maya Fernanda Dielsa (Ensiklopedia of Journal, 2023)
Labor monitoring, delivery mechanisms and care are important considered in order to monitor the welfare of the mother and fetus. Monitoring performed to assess the progress of labor, detect early emergencies and to make clinical decisions, care and medical action. In this case WHO recommends the use of the partograph as a means of monitoring labor standardized and most effective. The use of the partograph is carried out for all mothers in the active phase of the first stage of labor, used for all types of labour, on all places of delivery and by all birth attendants. Every helper Delivery is required to monitor and document carefully health and comfort of mother and fetus from the beginning to the end of labor. This research uses a descriptive research type with the method formative evaluation. The research respondents were all midwives who did birth assistance in Pasaman Barat District, 15  people. Data collection uses a partograph use statement by midwives in monitoring delivery in the form of a checklist filled in by researchers, then the data is processed using the percentage formula at each characteristic and given a predicate. The results of research on the use of partographs by midwives in every aid labor and partograph filling by midwives in monitoring labor in midwife in Pasaman Barat District, in 2022 dominated by sufficient predicate as much as 70%, then good predicate 25% and predicate less than 5%. This indicates in general that the use of and partograph included in the predicate adequate.